2021
DOI: 10.1002/lary.29474
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis Syndrome: Relapse and Tonsillar Regrowth After Childhood Tonsillectomy

Abstract: Objectives/Hypothesis Tonsillectomy is an effective treatment for periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome, but the role of adenoidectomy, as well as later tonsillar regrowth, is unclear. To find out if the volume of lymphoid tissue is pivotal to the efficacy, we analyzed the association between the relapse of the symptoms of PFAPA syndrome and regrowth of tonsillar tissue after tonsillectomy or adenotonsillectomy. Study Design Prospective cohort study of operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It has been suggested that the volume of the removed tonsillar tissue could be crucial in the efficacy of operative treatments in PFAPA syndrome. 26,27 In this trial, the amount of removed tonsillar tissue was often small, adenoids were left untouched, and the effect on PFAPA symptoms was still evident. In addition to the volume of the tonsils, localization of the removed tissue may be important.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It has been suggested that the volume of the removed tonsillar tissue could be crucial in the efficacy of operative treatments in PFAPA syndrome. 26,27 In this trial, the amount of removed tonsillar tissue was often small, adenoids were left untouched, and the effect on PFAPA symptoms was still evident. In addition to the volume of the tonsils, localization of the removed tissue may be important.…”
Section: Discussionmentioning
confidence: 84%
“…The mechanisms of the effectiveness of tonsil surgery in PFAPA syndrome are not known. It has been suggested that the volume of the removed tonsillar tissue could be crucial in the efficacy of operative treatments in PFAPA syndrome 26,27 . In this trial, the amount of removed tonsillar tissue was often small, adenoids were left untouched, and the effect on PFAPA symptoms was still evident.…”
Section: Discussionmentioning
confidence: 91%
“…Regrowth of the tonsillar tissue is also proposed to play a role in those with continued symptoms after tonsillectomy [42]. Five (5%) of 94 children in Finnish cohort had continued flares after tonsillectomy; most of these five patients had relapse of symptoms years after tonsillectomy.…”
Section: New Data On Treatment Strategiesmentioning
confidence: 99%
“…Characterizing risk variants for both PFAPA and SURF and understanding whether particular risk variants may predict response to tonsillectomy may shed light on differences and similarities in their pathogenesis. Interestingly, tonsillectomy alone led to complete episode resolution in two cohorts of patients with PFAPA [42,44 ▪ ], suggesting that adenoidectomy may not been needed and that the adenoids do not play as significant of a role in disease pathogenesis.…”
Section: New Data On Treatment Strategiesmentioning
confidence: 99%
“…Aside from traditional tonsillitis, intracapsular tonsillectomy has been used for symptomatic relief for active mononucleosis with massive tonsillar hypertrophy [23]. In addition, it has very recently been introduced for successful management of periodic fever, aphthous stomatitis, pharyngitis, and adenitis, or PFAPA [24,25 ▪ ].…”
Section: Expanding Indicationsmentioning
confidence: 99%